The Level of Cybersecurity Awareness among Graduate Female Students at King Saud University - Altayeb, Ahad Abdulkader; Alwahbi, Najla Turki; Almoqren, Noura Ahmed (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the level of cybersecurity awareness among female graduate students in the Curriculum and Instruction Department at the College of Education, King Saud University. This was achieved by assessing their awareness of cybersecurity concepts, their awareness of cybersecurity applications, and the key strategies to enhance cybersecurity awareness from their perspective. To achieve the study’s objectives, a descriptive survey methodology was employed, utilizing a questionnaire consisting of 30 statements distributed across three axes: awareness of cybersecurity concepts, awareness of cybersecurity applications, and strategies for enhancing cybersecurity awareness. The study’s key findings revealed that the participants demonstrated a high level of awareness regarding cybersecurity concepts. Similarly, they exhibited a high level of awareness concerning cybersecurity applications. Additionally, the participants strongly agreed on the importance of strategies for enhancing cybersecurity awareness. Based on these findings, the study recommended the development of training programs aimed at increasing cybersecurity awareness among female graduate students in universities.
Keywords: Cybersecurity Awareness; Cybersecurity in Universities; Graduate Studies